2017
DOI: 10.3928/01477447-20170621-01
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Efficiency of Anterior Cruciate Ligament Reconstruction in Outpatient Surgical Center Versus Hospital Operating Room

Abstract: Anterior cruciate ligament (ACL) reconstructions are complex orthopedic procedures in which a proficient team is of vital importance. Outpatient surgical centers (OSCs) often provide orthopedic-specific teams; however, hospital operating rooms (ORs) commonly rotate staff. The purpose of this study was to compare the efficiency of pediatric ACL reconstructions between a surgical center and a hospital OR owned and directed by a single institution. Cases examined involved pediatric patients, aged 12 to 18 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Although previous orthopaedic studies have investigated how surgery center ownership affects procedure utilization and time efficiency in the OR, this is the first to show evidence of cost savings for outpatient procedures performed in privately owned ambulatory surgery centers. 25,27 This finding is consistent with other recent literature showing that physician-owned hospitals provided cost savings for patients undergoing posterior lumbar fusion. 19 The comparison of operative times showed an association between high facility volume and shorter operative time for arthroscopic Bankart repair.…”
Section: Discussionsupporting
confidence: 91%
“…Although previous orthopaedic studies have investigated how surgery center ownership affects procedure utilization and time efficiency in the OR, this is the first to show evidence of cost savings for outpatient procedures performed in privately owned ambulatory surgery centers. 25,27 This finding is consistent with other recent literature showing that physician-owned hospitals provided cost savings for patients undergoing posterior lumbar fusion. 19 The comparison of operative times showed an association between high facility volume and shorter operative time for arthroscopic Bankart repair.…”
Section: Discussionsupporting
confidence: 91%
“…38 Outpatient ACL reconstruction is more efficient and results in lesser economic costs to providers while yielding equivalent or improved patient satisfaction, strength, and knee function. 21,43 The 2013 changes to health care regulations in the United States mandated that providers receive decreased compensation or reimbursement in cases where patients were readmitted within 30 days of initial discharge. 12,19,33 As such, it is important to identify risk factors that may contribute to adverse events in the immediate postoperative period.…”
mentioning
confidence: 99%
“…We hypothesize that private ASCs may be better equipped to provide orthopaedic-specific teams with greater knowledge of the tools and techniques being used. A previous study of anterior cruciate ligament reconstruction (ACLR) 18 found greater procedural efficiency at private ASCs compared with their hospital counterparts. A study of supracondylar humeral fractures 19 found that surgeries performed at a physician-owned ASC were more efficient and more cost-effective than surgeries performed at a hospital outpatient department.…”
Section: Discussionmentioning
confidence: 98%